Contractile Properties of MHC I and II Fibers From Highly Trained Arm and Leg Muscles of Cross-Country Skiers - Gejl, Kasper Degn; Hvid, Lars G.; Andersson, Erik P.; Jensen, Rasmus; Holmberg, Hans-Christer; Ørtenblad, Niels (Frontiers in Physiology, 2021)
Introduction: Little is known about potential differences in contractile properties of muscle fibers of the same type in arms and legs. Accordingly, the present study was designed to compare the force-generating capacity and Ca2+ sensitivity of fibers from arm and leg muscles of highly trained cross-country skiers. Method: Single muscle fibers of m. vastus lateralis and m. triceps brachii of 8 highly trained cross-country skiers were analyzed with respect to maximal Ca2+-activated force, specific force and Ca2+ sensitivity. Result: The maximal Ca2+-activated force was greater for MHC II than MHC I fibers in both the arm (+62 %, P < 0.001) and leg muscle (+77 %, P < 0.001), with no differences between limbs for each MHC isoform. In addition, the specific force of MHC II fibers was higher than that of MHC I fibers in both arms (+41 %, P = 0.002) and legs (+95 %, P < 0.001). The specific force of MHC II fibers was the same in both limbs, whereas MHC I fibers from the m. triceps brachii were, on average, 39% stronger than fibers of the same type from the m. vastus lateralis (P = 0.003). pCa50 was not different between MHC I and II fibers in neither arms nor legs, but the MHC I fibers of m. triceps brachii demonstrated higher Ca2+ sensitivity than fibers of the same type from m. vastus lateralis (P = 0.007). Conclusion: Comparison of muscles in limbs equally well trained revealed that MHC I fibers in the arm muscle exhibited a higher specific force-generating capacity and greater Ca2+ sensitivity than the same type of fiber in the leg, with no such difference in the case of MHC II fibers. These distinct differences in the properties of fibers of the same type in equally well-trained muscles open new perspectives in muscle physiology.